Polskie władze administracyjne w procesie wysiedlania ludności niemieckiej w latach 1945-1949. - Kacprzak, Paweł (Wydawnictwo Poznańskie sp. z o.o., 2010)
The decision about the displacement of Germans agreed in Potsdam protocols imposed certain obligations on the administrative organs of the states that were to supervise their transfers. Those obligations included adherence to certain standards of how the transfers were to be organised and humanitarian treatment of the persons being displaced. Those and other details were subsequently set out in various bilateral agreements. The execution of the agreed decisions was subject to control by special bodies of military missions. However, full adherence to the prescribed standards required substantial resources (transport, catering, qualified personnel) which only a stable state was capable of providing. Poland, badly damaged and impoverished after the war, did not meet the required standards. Consequently, the actual realisation of the Potsdam decisions and the displacement operation was not quite as expected. Hence the complaints and criticism of organisational inefficiency and non-humanitarian treatment of the population being displaced. It must be noted though that the central authorities tried hard and did their best to secure adequate fulfilment of their obligations, despite the frequently objective difficulties and conditions that rendered the task impossible to fulfil satisfactorily. Therefore, the critical assessment of the performance of the operation by Polish authorities should take into account the mitigating circumstances described above.
POLISH ADMINISTRATIVE AUTHORITIES IN THE PROCESS OF THE DISPLACEMENT OF GERMANS BETWEEN 1945 AND 1949.
Keywords: ustrój Polski; 1945-1949; wysiedlenia; ludność niemiecka